Healing of large periapical lesions following delivery of dental stem cells with an injectable scaffold: New method and three case reports - Vahab Shiehzadeh; Farhad Aghmasheh; Farideh Shiehzadeh; Mohammad Joulae; Emad Kosarieh; Farid Shiehzadeh (Wolters Kluwer Medknow Publications, 2014)
Regenerative endodontics is the creation and delivery of tissues to replace diseased, missing, and traumatized pulp. A call for a paradigm shift and new protocol for the clinical management of these cases has been brought to attention. These regenerative endodontic techniques will possibly involve some combination of disinfection or debridement of infected root canal systems with apical enlargement to permit revascularization and use of stem cells, scaffolds, and growth factors. Mesenchymal stem cells (MSCs) have been isolated from the pulp tissue of permanent teeth (dental pulp stem cells (DPSCs)) and deciduous teeth (stem cells from human exfoliated deciduous teeth). Stem cells are characterized as multipotent cells for regeneration.These three case reports describe the treatment of necrotic or immature teeth with periradicular periodontitis, which was not treated with conventional apexification techniques. All cases presented here developed mature apices and bone healing after 3 to 4 months after the initial treatment without complications, and faster than traditional treatments. Our clinical observations support a shifting paradigm toward a biologic approach by providing a favorable environment for tissue regeneration. The mechanism of this continued development and formation of the root end and faster tissue healing is discussed.